Corn Yield Loss Due to Volunteer Soybean. Issue 3 (September 2016) - Alms, Jill; Clay, Sharon A.; Vos, David; Moechnig, Michael
Abstract : The widespread adoption of glyphosate-resistant corn and soybean in cropping rotations often results in volunteer plants from the previous season becoming problem weeds that require alternative herbicides for control. Corn yield losses due to season-long volunteer soybean competition at several densities in two growing seasons were used to define a hyperbolic yield loss function. The maximum corn yield loss observed at high volunteer soybean densities was about 56%, whereas, the incremental yield loss ( I ) at low densities was 3.2%. Corn yield loss at low volunteer soybean densities was similar to losses reported for low densities of velvetleaf and redroot pigweed, with 10% yield loss estimated to occur at 3 to 4 volunteer soybean plants m −2 . Several herbicides, including dicamba with or without diflufenzopyr applied at the V2 growth stage of volunteer soybean, provided > 90% control, demonstrating several economical options to control volunteer glyphosate-resistant soybean in glyphosate-resistant corn. Reevaluation of control recommendations may be needed with commercialization of other genetically modified herbicide-resistant soybean varieties.